Trajetórias de Educadoras da Escola Jardim Beija Flor, Município de Luzinópolis-TO: tecendo histórias de vidas - Wagna, Lindemberg Costa Lucas (Universidade Federal do Tocantins, 2022)
The article aims to present the reflections made in the research stories of educators of the Beija Flor school from the municipal network of Luzinópolis, Tocantins. The objective was to analyze the educators' life stories, especially the analysis of the choice of profession, experiences, difficulties and challenges in teaching. The methodology developed was oral history, with life history techniques and semi-structured interviews with five educators (05). The criterion for choosing this school was because it was the first school in the municipality and the choice for being educators occurred because this school had female educators in its staff. The research indicated that the educators initially did not want to be trained in education; they did not choose to be teachers. However, this was the only opportunity they had and it led them to teaching. However, after they started working in education, they awakened a commitment to the education of children. The difficulties presented by the five interlocutors are related to the parents' lack of commitment to their children's education, and many students show a lack of interest in the classroom, hindering the progress of learning.